Eneolithic cultures of central and west Balkans - Tasić, Nikola (Belgrade : Draganić, 1995)
Rezime.
Bibliografija: str. 175-190.
Bilješke: str. 93-101.
Dar prof. Nives Majnarić-Pandžić.
Keywords: eneolitik; Vučedol; arheloška nalazišta